Vertical Scar Mammaplasty (Springer Berlin Heidelberg, 2018)
Vertical scar mammaplasty has now gained wide popularity, and important advances have been achieved since the successful first edition of this book, which described the fundamentals of the technique. This new, completely revised and updated edition fully reflects the evolution in vertical scar mammaplasty during the past decade. Previously published procedures have been modified and refined, and a variety of important newer techniques are presented. These include several breast reduction procedures using a short scar and techniques of mastopexy that pay specific attention to enhancement of breast projection and upper fullness. Extensive consideration is also given to the treatment of complications and the management of suboptimal outcomes of breast reduction and mastopexy. An impressive list of international authors have contributed to the book, each describing their own technique step by step in the manner of a manual. Not only are the surgical techniques precisely depicted in high-quality illustrations, but readers will have access to videos that will enable them to shorten their learning curve. Vertical Scar Mammaplasty will be an ideal guide to short scar breast surgery for trainees, and a superb reference for more experienced practitioners.